Effects of rosemary extract and its residue on production, immune performance, and gut microbiota in geese - Huang, Yuzhi; Xu, Lanmeng; He, Hang; Peng, Lijuan; Liao, Qinfeng; Wan, Kun; Qin, Simeng; Cao, Lijing; Zhang, Jie (Frontiers in Microbiology, 2025)
IntroductionTo explore the effects of rosemary extract (RE) and its residue (RR) on the production, immune performance, and gut microbiota of geese.MethodsWe treat 28-day-old Sichuan white geese (n = 180) with three diets: (1) basal diet (control), (2) basal diet supplemented with 0.02% RE, and (3) basal diet supplemented with 15% RR for 42 days.Results and discussionOn day 70, compared with control treatment, the final body weight, average daily gain and lysozyme levels in the RE treatment increased significantly (p < 0.05). In the RE and RR treatments, there was a significant decrease in alkaline phosphatase, globulin, and high-density lipoprotein levels compared to the control treatment, and there was also a significant increase in aspartate aminotransferase/alanine aminotransferase (p < 0.05). Moreover, for both RE and RR treatments, semi-eviscerated, eviscerated weights, and calcium apparent digestibility increased significantly, along with a decrease in the duodenal index (p < 0.05). Compared with RE treatment, those in the RR treatment had significantly higher duodenal and jejunum relative lengths, aspartate aminotransferase, uric acid, total cholesterol, and low-density lipoprotein levels, and decreased chest depth, chest angle, neck length, semi-eviscerated and eviscerated weights, crude protein digestibility, and levels of globulin, triglyceride, and lysozyme (p < 0.05). There were no differences in gut microbiota α or β diversities among treatments (p > 0.05). Compared to the control treatment, the relative abundance of Turicibacter significantly increased in the RR and RE treatments, and the relative abundance of Sporobacter, Alistipes, and Barnesiella significantly increased in the RR treatment (p < 0.05). Rikenellaceae, Succinivibrionaceae, and Aeromonadales were enriched in the RR treatment, and Lachnospiraceae, Turicibacteraceae, Fusobacteriaceae, and Enterobacteriaceae were enriched in the RE treatment. While we demonstrate the RR diet to be less effective than the RE diet, it did improve production and the gut microbiota of geese to a certain extent.